Community Service Oral Health Status Check - Legita, Nyayu Suci; Yolanda, Senli; Hastuti , Hevy; Sakdiyah , Jumiatul; Sistrianti, Sistrianti; Habibi, Julius (Universitas Dehasen Bengkulu, 2025)
instilling a clean and healthy life both in general health and dental health is the right thing. Dental health of children, it is very important for parents and school teachers to monitor the child's oral hygiene regularly. One way to realize is by detecting caries early. The purpose of this service is to get an idea of the level of tooth decay and motivation to do fillings by checking and monitoring dental health. This method of community service begins with the preparation stage, namely licensing, compiling work programs. Furthermore, the stages of implementing the activity began with screening the child's dental health status using the RTI and PTI indexes. Clinical examination of decay-teeth, missing-teeth and filling-teeth components was carried out by 9 children. The DMF-T index has an average of 4.77, meaning that the severity of caries is in the high category. The most PTI in the category is bad (99.4%) and the most RTI in the bad category (54%). The role of dental health workers is very important to achieve the 2030 caries-free policy through UKGS activities. So it is necessary to have continuous cooperation with dental health workers to improve the degree of dental health to avoid the occurrence of dental and oral diseases